PENGARUH MODEL PEMBELAJARAN DISCOVERY DAN MOTIVASI TERHADAP HASIL BELAJAR SENI RUPA SISWA KELAS VIII SEKOLAH MENENGAH PERTAMA NEGERI 31 PADANG - M.LUCKY ANDHRIEANSYAH, Dr. Ramalis Hakim, M.Pd., Dra. Ernis, M.Pd. (Universitas Negeri Padang, 2019)
The researcher aims to find out whether there is an influence of Discovery Learning and motivation on student learning outcomes in learning Grade VIII of SMPN 31 Padang Fine Arts. The research subjects were class VII students of SMP 31 Padang. This will use quasi-experimental methods (quasi experimental) with factorial 2 x 2 research design. Data collection is done through learning motivation questionnaire instruments and learning outcomes tests to see index difficulties, reliability and reliability. Data analysis techniques are used, namely the processing stage of the subject of research and inductive analysis using the SPSS program v. 16. The results of the study concluded that the use of the discovery learning model had a positive effect on the results of learning art class VIII SMP 31 Padang.Keywords : Discovery Learning Model.